2020
DOI: 10.3390/ijerph17176296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Efficacy, Depression, and Anger on Health-Promoting Behaviors of Korean Elderly Women with Hypertension

Abstract: The prevalence of hypertension among women in Korea aged 65 years or older is 61.7%. Past research has emphasized the importance of health-promoting behaviors in hypertension management for the elderly. The purpose of this cross-sectional study was to identify the effects of self-efficacy, depression, trait anger, and anger expression on the health-promoting behaviors of elderly women with hypertension. Self-report questionnaires were completed by 208 women aged 65 and older (age range: 65 to 85) diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
(39 reference statements)
2
23
0
1
Order By: Relevance
“…According to the interaction analysis, we found that the impacts on urban and rural areas was significant. Ae et al’s study found that depression was a risk factor in health-promoting behaviors, and that the engagement level in health-promoting behaviors increased as the depression level decreased in the low-income ordinary elderly hypertensive patients [ 61 , 62 ]. Elderly people with poor functional status are at higher risk of depression in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…According to the interaction analysis, we found that the impacts on urban and rural areas was significant. Ae et al’s study found that depression was a risk factor in health-promoting behaviors, and that the engagement level in health-promoting behaviors increased as the depression level decreased in the low-income ordinary elderly hypertensive patients [ 61 , 62 ]. Elderly people with poor functional status are at higher risk of depression in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…This study is consistent with previous studies that cited the importance of self-efficacy in health promotion activities in older adults and demonstrated that older adults who have more confidence, are more competent to manage their health, and are more likely to regularly engage in health promotion activities [ 3 , 7 ]. Studies also found that self-efficacy is an indicator for predicting important health outcomes such as healthy eating, oral health, and hypertension prevention in different populations [ 24 , 25 ]. The findings support the importance of self-efficacy for engaging in community-based activities and should be considered in interventions to increase the continuous participation rate [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 Nine studies did not mention that there was intentional non-adherence to factors affecting selfefficacy in hypertension treatment. 21,[23][24][25][26][27]29,30…”
Section: Finding 1: Intentional Non-compliancementioning
confidence: 99%